2022
DOI: 10.20517/mrr.2022.04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intrapartum antibiotics on the developing microbiota: a review

Abstract: The perinatal period sets the basis for the later physiological and immune homeostasis of the individual, with the intestinal microbiota being an important contributor to driving this homeostasis development. Therefore, the initial establishment and later development of the microbiota during early life may play a key role in later health. This early establishment of the intestinal microbiota is known to be affected by several factors, with gestational age, delivery mode, and feeding habits being extensively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Two seminal studies demonstrated the impact of IAP on the prevalence of ARGs and mobile elements in vaginally-delivered full-term babies, showing also a beneficial effect of breastfeeding on the ARGs burden 15 , 129 . Most of the current studies concluded that the selective pressure exerted by IAP favors the presence of different bacteria carrying ARGs, most of them species belonging to Pseudomonadota phyla or Staphylococcus genus 128 . In addition, IAP has also been associated with increments of ARGs in other body microbiomes, such as the nasopharynx and oral microbiota 128 .…”
Section: Factors Affecting Antibiotic Resistance In Infantsmentioning
confidence: 90%
See 2 more Smart Citations
“…Two seminal studies demonstrated the impact of IAP on the prevalence of ARGs and mobile elements in vaginally-delivered full-term babies, showing also a beneficial effect of breastfeeding on the ARGs burden 15 , 129 . Most of the current studies concluded that the selective pressure exerted by IAP favors the presence of different bacteria carrying ARGs, most of them species belonging to Pseudomonadota phyla or Staphylococcus genus 128 . In addition, IAP has also been associated with increments of ARGs in other body microbiomes, such as the nasopharynx and oral microbiota 128 .…”
Section: Factors Affecting Antibiotic Resistance In Infantsmentioning
confidence: 90%
“…Most of the current studies concluded that the selective pressure exerted by IAP favors the presence of different bacteria carrying ARGs, most of them species belonging to Pseudomonadota phyla or Staphylococcus genus 128 . In addition, IAP has also been associated with increments of ARGs in other body microbiomes, such as the nasopharynx and oral microbiota 128 .…”
Section: Factors Affecting Antibiotic Resistance In Infantsmentioning
confidence: 90%
See 1 more Smart Citation
“…Their results showed that colonization by Bi dobacteria was detected in fewer No-IAP neonates than in IAP neonates. The topic was followed by more than 20 culture-independent bacteriological studies investigating IAP and gut microbiota development since 2015 (72). Only some of the studies evaluated the effect of IAP in the rst days after birth in full-term neonates (12,21,27,30,31,70,71,(73)(74)(75) 21) observed a decrease in Bi dobacterium and Bacteroides spp.…”
Section: Impact Of Iap On the Neonatal Fecal Bacteriome In The Rst We...mentioning
confidence: 99%
“…This practice also leads to a substantial increase in Enterobacteriaceae in the neonatal gut microbiota during the first weeks of life. The changes caused by IAP at the taxonomic level are comparable to those triggered by the direct administration of antibiotics to infants [ 115 ]. IAP has also been reported to cause changes in the load of ARGs in the gut microbiota of newborns.…”
Section: Impact Of Antibiotics On the Developing Microbiota Compositionmentioning
confidence: 99%